War in the Pacific - Overy, Richard; Foreword by Dye, Daie (London Carlton)
Setting the scene with the unprovoked Japanese attack on Pearl Harbor and the almost simultaneous attack on US bases on Guam and Wake Island, this title documents the bloody battles fought in the jungle islands of Guadalcanal and the Philippines and the seas of the Pacific.
Keywords: World War (1939-1945) -- United States -- Pacific Ocean